1963
DOI: 10.1029/jz068i011p03459
|View full text |Cite
|
Sign up to set email alerts
|

Sound channels in the atmosphere

Abstract: The mean temperature profile of the atmosphere indicates the probable existence of two horizontally distributed sound waveguides in the atmosphere. The lower one usually occurs between the surface and 50 km, and the upper between 50 and 110 km. Wind data above 30 km, which have become available recently through the use of meteorological rockets, have resulted in revised concepts of atmospheric circulation patterns for the northern hemisphere. Wind data obtained from these patterns have been combined with mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1964
1964
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The sound speed ͑C͒ is proportional to the square root of the absolute temperature (T in kelvin) of the atmosphere, i.e., C = ͱ ␥RT, where R is the molar gas constant ͑R = 8.3145 J / mol/ K͒, ␥ is the adiabatic index (1.4 for diatomic gas). The speed of acoustic waves ͑V͒ in a horizontally moving medium is (Diamond, 1963)…”
Section: Inversion For Atmospheric Temperature and Windsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sound speed ͑C͒ is proportional to the square root of the absolute temperature (T in kelvin) of the atmosphere, i.e., C = ͱ ␥RT, where R is the molar gas constant ͑R = 8.3145 J / mol/ K͒, ␥ is the adiabatic index (1.4 for diatomic gas). The speed of acoustic waves ͑V͒ in a horizontally moving medium is (Diamond, 1963)…”
Section: Inversion For Atmospheric Temperature and Windsmentioning
confidence: 99%
“…Acoustic waves with frequencies below 20 Hz, or infrasound, can propagate long distances with minimal intrinsic attenuation or dispersion (Diamond, 1963). This characteristic makes infrasound a powerful remote sensing tool for probing the atmosphere (Drob et al, 2003;Herrin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…There are two sound channels in the upper atmosphere (Diamond, 1963) in the upper stratosphere P around 50 km and in the lower thermosphere around 110 km. Donn and Rind (1972) showed that for microbaroms reflecting in the lower thermosphere the amplitudes of the microbarom siqnals exhibit a stronq semidiurnal fluctuation due to the presence of the semidiurnal tidal wind in the lower thermosphere.…”
Section: Theorymentioning
confidence: 99%
“…Thus a failure of the strict applicability of ray theory to this infrasonic case probably results in the apparent con- They go on to say, however, that the westerly flow that produces the strong acoustic inversion in the midlatitudes is much less pronounced at high latitudes. Diamond [1963] suggests that at 65øN latitude sound will be refracted back to the earth's surface in the winter only if it is propagating from a direction whose azimuth lies between 180 ø and 360 ø (i.e., it must have a west to east component). Pridmore-Brown [1962] has shown that there are great asymmetries introduced in the distribution of the zones of silence, which surround a surface source of sound,.…”
Section: Only the Usual Fnmafolio Activity Has Been Reported For Augumentioning
confidence: 99%